The identification and ennoblement of 'hybridity' during the Iberian Union 1580–1640. Issue 4 (29th July 2019) - Roe, Jeremy
Abstract: The Arch of the Portuguese designed by the scholar and physician Luis Nunes is the focus of this article and it provides a case study for the analysis of the representation of hybrid Iberian identities. Drawing on recent studies on early modern hybridity, identity and composite monarchy this study develops an original reading of Nunes's arch design, as well as other examples of Iberian visual culture, in terms of the negotiation of political status and the articulation of hybrid identities.